Physicochemical components, antioxidant activity, and predictive models for quality of soursop tea (Annona muricata L.) during heat pump drying - Vu Ngoc Duc; Diep Duong Thi Ngoc; Nguyen Nhat An; Long Huynh Bao; Pham Binh An (Open Chemistry)
The peel and pulp of soursop are ideal for creating a new tea product, offering a unique flavor compared to traditional leaf tea. This study develops mathematical models to describe the drying process, decomposition of bioactive components, and antioxidant activity of soursop slices. The slices were dried at four temperatures (20–50°C) using industrial-scale heat pump drying. Changes in moisture ratio (MR) were calculated and compared with 30 previous models. Additionally, two and four mathematical models were used to analyze data on total flavonoid content (TFC) and antioxidant activity. The model fits were evaluated based on statistical parameters (R 2, root mean square error, χ 2). The results indicated that the drying process at 20°C involved two mechanisms following the Aghbashlo model (R 2 > 0.993). At higher temperatures, the moisture removal process followed a single mechanism. Zero order, first order, and polynomial quadratic models were suitable for describing TFC decomposition and antioxidant activity, depending on the temperature. The activation energy of MR (29.89 kJ/mol) was lower than that of 2,2′–azino-bis–3–ethylbenzothiazoline–6–sulfonic acid (37.02 kJ/mol) and 2,2–diphenyl–1-1-picrylhydrazyl (32.12 kJ/mol), indicating drying efficiency and retention of bioactive components. The study’s findings are expected to enhance quality, improve economic efficiency, and expand the market for soursop tea.